Pengaruh Financial Distress, CSR Disclosure, Dan Earnings Quality Terhadap Firm Value Yang Dimoderasi Liquidity - Aprilia Zahra Adisti; Nera Marinda Machdar (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research aims to examine the influence of financial distress, corporate social responsibility disclosure and earnings quality on firm value with liquidity as a moderating variable. This type of research uses a qualitative descriptive method for literature study. The research results show that financial distress has a positive effect on firm value; corporate social responsibility disclosure has a positive effect on firm value; earnings quality has a positive effect on firm value; liquidity can strengthen the influence of financial distress on firm value; liquidity can strengthen the influence of corporate social responsibility disclosure on firm value and liquidity can strengthen the influence of earnings quality on firm value.